2014
DOI: 10.1002/hrdq.21192
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Organizational Commitment: The Mediating Role of Job Characteristics

Abstract: Although the contribution of transformational leadership to employee organizational commitment is well documented, the mechanisms that explain such relationship remain unclear. In the present research, we propose that transformational leadership can influence organizational commitment through impacting followers’ perceptions of job characteristics (i.e., feedback from job, task variety, and decision‐making autonomy). Structural equation modeling analyses conducted on a sample of employees from multiple organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 142 publications
(162 reference statements)
5
61
0
4
Order By: Relevance
“…There are various organizational personnel in hospitals, so it may be difficult for nurse managers to exert their leadership and increase motivation towards a common goal. TLB helps to motivate organization members to achieve outcomes beyond personal interests and to recognize the value of their work [21,22]. Nurse managers, therefore, need to provide sensitive attention and instill persistent beliefs in order to help staff nurses to have confidence in their nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…There are various organizational personnel in hospitals, so it may be difficult for nurse managers to exert their leadership and increase motivation towards a common goal. TLB helps to motivate organization members to achieve outcomes beyond personal interests and to recognize the value of their work [21,22]. Nurse managers, therefore, need to provide sensitive attention and instill persistent beliefs in order to help staff nurses to have confidence in their nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…Hackman and Oldham () operationalized job characteristics as a high‐order construct and argued that this measure may provide more convincing explanations in the context of organizational research. Accordingly, using this most commonly used measure, subsequent research has revealed that job characteristics represent a superordinate construct because the five dimensions display high related loadings (e.g., Chen & Kao, ; Gillet & Vandenberghe, ). Therefore, in the present study, we treat job characteristics as a whole construct with an estimated internal consistency of the scale scoring α = 0.82.…”
Section: Methodsmentioning
confidence: 99%
“…This study developed and tested the conceptual model of job satisfaction using SEM as well as a framework for the implementation of job characteristics, organizational commitment, and job satisfaction in construction companies in Taiwan that hire foreign workers. This cross-cultural empirical research contributes to the existing literature, following the recommendation of Gillet and Vandenberghe (2014) that further research on cross-cultural issue should be conducted with employees to replicate and extend these findings. The SEM results of this study indicated that job characteristics positively affect organizational commitment.…”
Section: Discussionmentioning
confidence: 87%